2007
DOI: 10.1111/j.1523-5378.2007.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Stimulates a Mixed Adaptive Immune Response with a Strong T‐Regulatory Component in Human Gastric Mucosa

Abstract: The cytokine profile of H. pylori-infected gastric mucosa shows a mixed Th1-Th2 profile. Furthermore, a high IL10 expression may indicate that also regulatory T cells play a role in the chronic phase of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 42 publications
6
68
2
Order By: Relevance
“…They further showed that people with ulcers had reduced Treg responses and increased Th1 and Th2 responses compared with those without ulcers. These studies suggest a protective role for TGF-␤ and Tregs, but there are also some studies indicating that Tregs induced during H. pylori infection may promote prolonged infection, and these studies lend support to the notion that Tregs are important in the chronicity of infection (12). Another group demonstrated that memory T cells from infected individuals did not respond well to H. pylori membrane preparations compared to memory cells from uninfected individuals, but the activity was restored in infected individuals when Tregs were depleted (24).…”
Section: Discussionmentioning
confidence: 61%
“…They further showed that people with ulcers had reduced Treg responses and increased Th1 and Th2 responses compared with those without ulcers. These studies suggest a protective role for TGF-␤ and Tregs, but there are also some studies indicating that Tregs induced during H. pylori infection may promote prolonged infection, and these studies lend support to the notion that Tregs are important in the chronicity of infection (12). Another group demonstrated that memory T cells from infected individuals did not respond well to H. pylori membrane preparations compared to memory cells from uninfected individuals, but the activity was restored in infected individuals when Tregs were depleted (24).…”
Section: Discussionmentioning
confidence: 61%
“…It has become clear that hosts that mount a strong proinflammatory response are more likely to develop severe complications of disease, such as peptic ulcers or neoplasia (17), although the factors that determine which hosts will develop such responses remain unclear. In fact, the most recent evidence suggests that in humans, the primary response to infection is actually immunoregulatory (18)(19)(20)(21)(22). This finding supports many years of animal research indicating that suppression of regulatory responses is necessary for induction of severe disease (11,(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 53%
“…IL-1β have a major role in the initiation of the host immune response against H. pylori infections. The mRNA expression of IL-1β was shown to increase in patients (28)(29)(30). In addition to IL-1β, the inflammatory cells also secrete TNF-α during H. pylori-induced inflammation (31).…”
Section: Discussionmentioning
confidence: 98%